Vitamin D Supplements and Prevention of Cancer and Cardiovascular Disease - Manson, JoAnn E; Cook, Nancy R; Lee, I-Min; Christen, William; Bassuk, Shari S; Mora, Samia; Gibson, Heike; Gordon, David; Copeland, Trisha; D’Agostino, Denise; Friedenberg, Georgina; Ridge, Claire; et al. (The New England journal of medicine, 2019)
This article reports the vitamin D portion of a randomized, two-by-two factorial trial of n−3 fatty acids and vitamin D in the prevention of cancer and cardiovascular disease. Vitamin D did not result in a lower incidence of invasive cancer or cardiovascular events than placebo.